Mental Symptoms and Stress of Hospitalized Schizophrenia Patients With 2019 Novel Coronavirus Disease: An Observation Study - Ma, Jun; Jiang, Tao; Huang, Hanjun; Li, Ruihua; Zhang, Lin; Liu, Lianzhong; Liu, Xuebing (Frontiers in Psychiatry, 2021)
Background: The 2019 novel coronavirus disease (COVID-19) is an extremely rapidly spreading respiratory infection caused by SARS-CoV-2. Many schizophrenic patients were infected with COVID-19 in Wuhan City, Hubei Province. This study took hospitalized schizophrenia patients with COVID-19 as the research subjects and observed the changes in psychopathology and stress of patients with COVID-19 and the accompanying social isolation. Methods: To sort and isolate potential COVID-19-infected patients, an isolated ward was set up from January 30, 2020, to March 30, 2020. Schizophrenia patients with COVID-19 were referred to this ward, and long-term hospitalized cases were included in this study. The Positive and Negative Syndrome Scale and Perceived Stress Scale were used to evaluate the severity of mental symptoms and psychological stress in the early stage of the outbreak of COVID-19, after the diagnosis of COVID-19 and after recovery. At the time of diagnosis, we also extracted the patient's routine blood, biochemical and other indicators and asked the patient's perception of COVID-19. Results: 21 hospitalized schizophrenia patients with COVID-19 were recruited in this study. The changes in PANSS scores were not significant (p = 0.225 baseline vs. diagnosed, p = 0.399 cured vs. diagnosed). The CPSS scores increased significantly after diagnosis and transfer to the isolation ward (p < 0.001 baseline vs. diagnosed, p < 0.001 cured vs. diagnosed). The course of schizophrenia was a protective factor of stress levels to cases (t = −3.25, p = 0.006), and patients' perception of COVID-19 was a risk factor (t = 2.48, p = 0.038). The final multiple linear regression model was statistically significant (F = 8.16, p < 0.001). Conclusion: Hospitalized schizophrenia patients with COVID-19 had increased stress levels and negative symptoms but alleviated positive symptoms after medical isolated treatment. This reminds us that in the face of major epidemics, we must specifically alleviate the psychological burden at the peak of the epidemic and improve the prognosis of patients after the epidemic.